Systematics, phylogeography and polyploid evolution in the Dactylorhiza maculata complex (Orchidaceae) - Ståhlberg, David (Department of Ecology, Lund University, 2007)
The aim of this thesis was to investigate and describe different aspects of variation in the Dactylorhiza maculata complex and to relate the variation patterns to underlying biological processes such as Quaternary migration history, hybridization and polyploid evolution. The variation patterns were analysed at various geographic levels using molecular markers (plastid DNA and ITS of nrDNA), cytological data, morphometry and ecological data. A total of c. 2 500 plants from almost 400 populations from throughout Europe were analysed. Dactylorhiza maculata s.l. is the maternal parent of many allotetraploid taxa. It was shown that allotetraploids in Scandinavia belong to several different widespread lineages that probably arose before the last glaciation. A minimum of three autotetraploid lineages were discerned in the D. maculata complex: (i) southern/western ssp. maculata, (ii) northern/eastern ssp. maculata and (iii) Central European ssp. fuchsii. The southern/western and northern/eastern lineages, which probably predate the last glaciation, form a contact zone in central Scandinavia. Measures of genetic diversity therefore reach high values in central Scandinavia. A high frequency of intermediate plastid haplotypes in the contact zone suggests that plastid DNA recombination is occurring there. Source areas for postglacial migration of ssp. maculata may have been Central Europe and parts of central Russia located between the Fennoscandian ice sheet and the Urals. Areas of sheltered topography in Central Europe may have provided suitable habitats for the more thermophilous ssp. fuchsii. A clinal differentiation in genetic markers from the south to the north was observed for ssp. fuchsii (including ssp. saccifera). The tetraploid lineage of ssp. fuchsii is poorly separated from diploid ssp. fuchsii and probably originated during the current postglacial period. The Mediterranean region and the Caucasus have not contributed to northward migration, neither for ssp. fuchsii, nor for ssp. maculata. Introgression between ...